Information, financial aid and training participation: Evidence from a randomized field experiment - Katja Görlitz; Marcus Tamm (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
To increase employee participation in training activities, the German government introduced a large-scale training voucher program in 2008 that reduces training fees by half. Based on a randomized field experiment, this paper analyzes whether providing information about the existence and the conditions of the training voucher had an effect on actual training activities of employees. Because the voucher was newly introduced, only one-fourth of the eligible employees knew the voucher exists at the time of the experiment. The information intervention informed a random sample of eligible employees by telephone about the program details and conditions. The results indicate that the information significantly increased treated individuals knowledge of the program but had no effect on voucher take-up or participation in training activities. Additional descriptive analyses suggest that the reasons for these zero effects are that the demand for self-financed training is low and that liquidity constraints do not discourage many employees from training participation.
Keywords: I22; D83; H52; 330; training participation; voucher; financial aid; randomized field experiment; information treatment